Nutrients against adipogenesis : aim to cheating age or weight reduction - Santiago Herrero (World Nutrition Journal, 2022)
Obesity is associated with increased risk of conditions such as type 2 diabetes, CHD, hypertension, dyslipidaemia (which are often included in the so-called metabolic syndrome), gall stones, certain types of cancer (breast and colon), osteoarthritis, non-alcoholic steatohepatitis, sleep apnoea, infertility, and many psychological conditions. Moreover, there is a marked reduction in life expectancy of the order of several years.